The effects of multiple storages on performance of hydro-pneumatic hybrid driveline - F., Wasbari; R. A., Bakar; Gan, Leong Ming; M. F., Sukri; H. N. M., Shah (Universiti Malaysia Pahang, 2018)
The study emphasis on the effect of multiple storages on the performance of hydro-pneumatic hybrid driveline. Passenger’s car space is very limited. Therefore, the initial solution suggested to use smaller storage, but more in numbers. Its small size allows it to be placed several locations in the car while the number increases the storage capacity. An experiment was carried out to see the system behaviour. It was found that the multiple storages produced better power. However, the torque and efficiency had an adverse effect because of the increase of motor speed, pressure drop, and flow limitation.